Chronic Inhibition of Renal Outer Medullary Potassium Channel Not Only Prevented but Also Reversed Development of Hypertension and End-Organ Damage in Dahl Salt-Sensitive Rats. Issue 2 (February 2017) - Zhou, Xiaoyan; Forrest, Michael J.; Sharif-Rodriguez, Wanda; Forrest, Gail; Szeto, Daphne; Urosevic-Price, Olga; Zhu, Yonghua; Stevenson, Andra S.; Zhou, Yuchen; Stribling, Sloan; Dajee, Maya; Walsh, Shawn P.; et al.
Abstract : The renal outer medullary potassium (ROMK) channel mediates potassium recycling and facilitates sodium reabsorption through the Na + /K + /2Cl − cotransporter in the loop of Henle and potassium secretion at the cortical collecting duct. Evidence from the phenotype of humans and rodents with functional ROMK deficiency supports the contention that selective ROMK inhibitors (ROMKi) will represent a novel diuretic with potential of therapeutic benefit for hypertension. ROMKi have recently been synthesized by Merck & Co, Inc. The present studies were designed to examine the effects of ROMKi B on systemic hemodynamics, renal function and structure, and vascular function in Dahl salt-sensitive rats. Four experimental groups—control, high-salt diet alone; ROMKi B 3 mg·kg − 1 ·d − 1 ; ROMKi B 10 mg·kg − 1 ·d − 1 ; and hydrochlorothiazide 25 mg·kg − 1 ·d − 1 —were included in prophylactic (from week 1 to week 9 on high-salt diet) and therapeutic studies (from week 5 to week 9 on high-salt diet), respectively. ROMKi B produced sustained blood pressure reduction and improved renal and vascular function and histological alterations induced by a high-salt diet. ROMKi B was superior to hydrochlorothiazide at reducing blood pressure. Furthermore, ROMKi B provided beneficial effects on both the plasma lipid profile and bone mineral density. Chronic ROMK inhibition not only prevented but also reversed the development of hypertension and end-organ damage in Dahl salt-sensitive rats. Our findings suggest a potential utility of ROMKi B as a novel antihypertensive agent, particularly for the treatment of the salt-sensitive hypertension patient population. Abstract : Supplemental Digital Content is available in the text.